1981
DOI: 10.1038/290343a0
|View full text |Cite
|
Sign up to set email alerts
|

Slow-reacting substances (leukotrienes) contract human airway and pulmonary vascular smooth muscle in vitro

Abstract: During a type I allergic reaction histamine, slow-reacting substance of anaphylaxis (SRS-A) and other mediator substances are elaborated from specific tissue sites. In allergic asthma these sites are in the lung and the mediator substances cause airway obstruction by contracting smooth muscle and altering mucociliary function. Unlike histamine, slow-reacting substances (SRSs) have been assessed very little for their roles in obstructive airways disease. This has been partly due to the fact that their chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
108
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(111 citation statements)
references
References 9 publications
2
108
1
Order By: Relevance
“…In the present study, the protocol described by Creese & Denborough (1981) The contraction induced by the addition of endothelin to the organ baths was extremely slow in onset. Its prolonged nature was similar to the contraction which results from the application of leukotrienes to isolated bronchial tissue (Hanna et al, 1981). Endothelin may therefore elicit contraction via endogenous leukotriene release.…”
Section: Autoradiographic Studiesmentioning
confidence: 55%
See 1 more Smart Citation
“…In the present study, the protocol described by Creese & Denborough (1981) The contraction induced by the addition of endothelin to the organ baths was extremely slow in onset. Its prolonged nature was similar to the contraction which results from the application of leukotrienes to isolated bronchial tissue (Hanna et al, 1981). Endothelin may therefore elicit contraction via endogenous leukotriene release.…”
Section: Autoradiographic Studiesmentioning
confidence: 55%
“…The effect of indomethacin Neither the potency nor the efficacy of the contraction generated by ET-1 was affected by 25 gM indomethacin ( was similar to that of leukotriene D4 (Hanna et al, 1981) and the thromboxane A2-mimetic U46619 (Armour et al, 1989), but far greater than that of carbachol and histamine . Its efficacy was however, less than that of carbachol and therefore of U46619 which produces a greater contractile response than carbachol in human airway tissue.…”
Section: Autoradiographic Studiesmentioning
confidence: 99%
“…The leukotrienes are known to cause bronchoconstriction in vivo and in vitro (Drazen, Austen, Lewis, Clark, Goto, Marfat & Corey, 1980;Hanna, Bach, Pare & Schellenberg, 1981) but the present experiments show that they may also act to enhance the effects of other bronchoconstrictor agents. Recent observations of an indomethacin-induced potentiation of histamine and arachidonic acid contractions of guinea-pig (Adcock & Garland, 1980;Mitchell, 1982) and human (Adcock & Garland, 1982) airway smooth muscle in vitro, have suggested that other lipoxygenase products may also increase airway reactivity.…”
Section: Discussionmentioning
confidence: 83%
“…A high probability of a significant role of p LTs in the immunological response of human pulmo nary tissue was further backed by the facts that the tissue has an ability to release a substantial amount of p-LTs immunologically (2,18) and the airway smooth muscle is highly responsive to p-LTs (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the slow reacting substance of anaphylaxis (SRS-A), which had been tentatively desig nated as p-LTs until identification of their structures, the p-LTs have been proven to be potent pulmonary tissue constrictors in some species, especially humans and guinea pigs (4)(5)(6)(7). Because human or guinea pig lungs possess a great ability for p-LT formation and their airway smooth muscles markedly respond to p LTs, p-LTs formed intrinsically may be largely re sponsible for the pulmonary tissue contractions during anaphylaxis.…”
mentioning
confidence: 99%